Association Between CD4⁺ T Cell Hyperfunction and Advanced Liver Injury in Chronic Liver Disease - Campeau, Natasha (Université d'Ottawa / University of Ottawa, 2024)
Chronic liver disease accounts for more than 2 million annual deaths worldwide and falls within the top 20 leading causes of death. Particularly, metabolic dysfunction-associated steatohepatitis (MASH) is now the leading cause of end-stage liver disease, surpassing viral hepatic infections. Over time, liver fibrosis impacts organ structures and function, and is increasingly associated with local and circulating immune cell dysfunction and systemic inflammation, collectively contributing to poor clinical outcomes. This thesis aimed to investigate CD4⁺ T cell function in the context of chronic liver disease in humans and in murine models that mimic HCV and MASLD pathologies. We hypothesized that in chronic liver disease, CD4⁺ T cell hyperfunction and increased intrahepatic infiltration are associated with advanced liver injury. In MASH patients, we found CD4⁺ T cell hyperfunction in those with advanced liver fibrosis, marked by increased TGF-β and IFN-γ production. Data collected from the diet-induced liver model suggest sex differences with transient CD4⁺ T cell hyperfunction in males, while hyperfunction in females sustained until 2 weeks post-HFMCDD cessation, characterized by elevated GrzB and IFN-γ expression. In addition to these findings, positive correlations were also observed between CD4⁺ and CD8⁺ T cell infiltration and liver injury severity. In conclusion, these findings suggest an association between CD4⁺ T cell hyperfunction and advanced liver injury in chronic liver disease.
Keywords: CD4 T cells; MASLD; HCV; Liver fibrosis; T cell hyperfunction; Steatohepatitis